Democrats’ Mistakes and the Birth of Authoritarian Rule: Ramón S. Castillo and the Fall of Conservative Democracy in Argentina - Taccone, Nicolás (2023)
On 4 June 1943, a military coup crushed Argentina´s democracy, marking the end of the oligarchic era and ‘planting the seeds’ of Peronism. This case sheds light on how rulers’ mistakes can operate as a key independent variable in producing regime changes. We argue that the former conservative president, Ramón S. Castillo, provoked an otherwise avoidable democratic breakdown. Specifically, Castillo´s misguided relationships with regime insiders and outsiders unintentionally eroded political stability and triggered the fall of democracy. Until now, agent-based scholarship has fallen short in tracing incumbents’ mistakes and linking them to regime-change processes. We test the argument by conducting a within-case analysis of Argentina´s democratic fall in the early 1940s, scrutinising the president´s errors at five critical events. We conclude that critical-event analysis can help disentangle the role of leaders’ mistakes in other episodes of regime change.